The Breathing IQ: an anthropometric index of diaphragmatic breathing efficiency - Vranich, Belisa; Lee, Rachel; Zapanta, John; Shoen, Brian; Houghton, Helene; Ruelas, Crystal; Wahlfeldt, Mary Lisa; Kerr, Robin; Pripotnev, Andrei; Goorahoo, Michaela; Baptiste, Jean-Berne; Elliot, Joanne (Frontiers in Physiology, 2025)
BackgroundBreathing pattern disorders (BPDs) are becoming increasingly relevant due to the rise of respiratory illnesses but are often limited to diagnoses of hyperventilation syndrome and do not consider breathing dysfunction of mechanical origin. Impaired diaphragmatic and inefficient breathing patterns often evolve into downstream musculoskeletal and psychological consequences. Respiratory research has consistently called for the standardization of methods that can consider breathing as multifactorial and also consider breathing mechanics.AimThis paper aims to introduce the Breathing IQ (BIQ) as a novel anthropometric index of abdominothoracic flexibility for identifying biomechanical breathing patterns and assessing diaphragmatic breathing efficiency.MethodA sample of N = 384 individuals was assessed with the BIQ pre- and post-intervention of five corrective exercises in a single 90-minute session to identify changes in the BIQ grade (A–F), as determined by measuring the breathing range of motion (ROM) and location of movement (LOM).ResultsBinary-grade improvement (yes/no) occurred in 331 of 370 without an A grade at baseline (89.5%), p < 0.001. Before the intervention, 249 (64.8%) were graded an F and only 14 (3.7%) were graded an A. After the intervention, only 20 (5.2%) were graded an F and 102 (26.6%) were graded an A. Breath hold (BH) improved from pre- to post-intervention, from 37.2 (18.7) to 66.0 (26.9), with a mean change 24.3 (15.3), which was highly significant (p < 0.001).ConclusionThe BIQ shows preliminary potential as an effective screening tool for mechanical breathing dysfunction.